Realising the Gains from Full Regional Connectivity in South Asia: the Transport Costs Dimension. - Prabir De (2008)
One of the impediments to the full regional connectivity in South Asia is the absence of integrated and improved cross-border transportation linkage. A task that heads of SAARC countries had identified is to reduce the trade transportation costs by integrating the region with an improved and uninterrupted connectivity. An understanding of the regional transportation costs is of particular interest because this would enable a better evaluation of the required cross-border transportation services so as to realise the gains of full regional connectivity in South Asia. This paper discusses the profile and magnitude of trade transportation costs for a set of South Asian countries. The general conclusion of this paper is that these costs across South Asia are very high and vary across goods and countries. The South Asian countries have been paying more towards trade transportation costs, compared to customs tariffs, and the cost of trade transportation increases if the country is landlocked. The paper reveals that South Asia’s land borders are highly congested and need special attention in order to reduce time delay and costs of transaction.